Migrants for Export: How the Philippine State Brokers Labor to the World - Choudry, Aziz (Labour / Le Travail, 2011)
The article reviews the book, "Migrants for Export: How the Philippine State Brokers Labor to the World," by Robyn Magalit Rodriguez.
Keywords: BOOKS – Reviews; FILIPINO foreign workers; MIGRANTS for Export: How the Philippine State Brokers Labor to the World (Book); Nonfiction; RODRIGUEZ; Robyn Magalit